Systemic Sclerosis Associated Angiosarcoma: A Case Report and Review of the Literature - Brittany Carter; Christine Jaworsky; Monte Fox (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2016)
Cutaneous angiosarcoma is an uncommon malignant vascular tumor with a highly variable presentation. It most commonly occurs on the head and neck of elderly Caucasian men, while less commonly on the skin of persons with pre-existing conditions or cutaneous lesions. To date, only three reports of angiosarcoma arising on the head and neck of individuals with systemic sclerosis exist in the literature. We report the fourth case: a 58 year-old African-American female with systemic sclerosis who developed an epithelioid subtype of cutaneous angiosarcoma on the right elbow, rather than the head and neck region.